Dopamine-dependent long-term depression at subthalamo-nigral synapses is lost in experimental parkinsonism - Dupuis, Julien Pierre; Feyder, Michael; Miguelez, Cristina; Garcia, Liliana; Morin, Stéphanie; Choquet, Daniel; Hosy, Eric; Bezard, Erwan; Fisone, Gilberto; Bioulac, Bernard H; Baufreton, Jérôme (The Journal of neuroscience, 2013)
Impairments of synaptic plasticity are a hallmark of several neurological disorders, including Parkinson's disease (PD) which results from the progressive loss of dopaminergic neurons of the substantia nigra pars compacta leading to abnormal activity within the basal ganglia (BG) network and pathological motor symptoms. Indeed, disrupted plasticity at corticostriatal glutamatergic synapses, the gateway of the BG, is correlated to the onset of PD-related movement disorders and thus has been proposed to be a key neural substrate regulating information flow and motor function in BG circuits. However, a critical question is whether similar plasticity impairments could occur at other glutamatergic connections within the BG that would also affect the inhibitory influence of the network on the motor thalamus. Here, we show that long-term plasticity at subthalamo-nigral glutamatergic synapses (STN-SNr) sculpting the activity patterns of nigral neurons, the main output of the network, is also affected in experimental parkinsonism. Using whole-cell patch-clamp in acute rat brain slices, we describe a molecular pathway supporting an activity-dependent long-term depression of STN-SNr synapses through an NMDAR-and D1/5 dopamine receptor-mediated endocytosis of synaptic AMPA glutamate receptors. We also show that this plastic property is lost in an experimental rat model of PD but can be restored through the recruitment of dopamine D1/5 receptors. Altogether, our findings suggest that pathological impairments of subthalamo-nigral plasticity may enhance BG outputs and thereby contribute to PD-related motor dysfunctions.